USP7 regulates growth and maintains the stemness of p53-mutant colorectal cancer cells via stabilizing of mutant p53 - Li, Xue; Pan, Jie; Zheng, Pengcheng (Frontiers in Oncology, 2024)
IntroductionTP53 is one of the most frequently mutated genes among all cancers, and TP53 mutants occur more than 40% in colorectal cancers (CRCs). Accumulation of mutant p53 may augment colorectal cancer stem cells (CCSCs) phenotype and enhance colorectal tumorigenesis. Thus, reducing the level of mutant p53 protein is an attractive anticancer strategy.MethodsCSC-enriched cancer cells were obtained by tumor sphere formation assay. The effects of USP7 on the proliferation of cancer cells were determined by MTS and colony formation assays. Wound healing assay was used to test cell migratory abilities. qPCR and western blotting assays were performed to verify the mRNA and protein levels of CSC markers, USP7 and p53. Co-immunoprecipitation assay was used to test the interaction effects between USP7 and p53.ResultsIn this study, we found that USP7 and mutant p53 were dramatically elevated in CSC-enriched colorectal cancer cells and USP7 expression was positively associated with self-renewal and maintenance of CCSCs. USP7 regulated cell growth, stemness and migration of colorectal cancer cells. USP7 depletion significantly reduced proliferation of cancer cells and suppressed the self-renewal of CSC-enriched colorectal cancer cells. Further studies indicated that USP7 knockdown could significantly decrease mutant p53 protein levels both in CRCs and CSC-enriched colorectal cancer cells. Moreover, mutant p53 was stabilized by USP7 and they interacted with each other. Furthermore, USP7 inhibitor P5091 also diminished CCSCs self-renewal and reduced mutant p53 levels.ConclusionTaken together, our findings demonstrated that USP7 involved in the modulation of CCSCs stemness, as well as a critical target for clinical treatment of cancers with different p53 mutations.